The fall. Series 3 [videorecording (DVD)] - Cubitt, Allan (Acorn Media, 2017)
DSI Stella Gibson continues her game of cat and mouse with serial killer Paul Spector in the third series of this smart psychological thriller. She has arrested Spector, but will he survive the gunshot wounds? Will he ever face justice?